Protection of industrial designs in the Andean Community countries and The Hague Agreement System - Barreto Guinea, Ana Teresa (2022)
This paper intends to develop the topics related to (i) the importance of the protection of industrial rights; (ii) the national, supranational and international regulatory framework on the protection of industrial and intellectual property, with a special focus on Decision 486 of the Andean Community and Legislative Decree 1075; (iii) the Hague Agreement, the international treaty that governs the international registration of industrial designs in various countries, through a central registry; and, (iv) the international system of the Hague Agreement, which makes it possible to grant protection to industrial designs in various countries or regions with a minimum of formalities.